Springboard: student book; T1 - Jack C Richards (Oxford Univ. Press, 1997)
The book is organized around high-interest topics that encourage students to talk about what they are most interested in: their own lives, aspirations, and interests. It activates both previous language knowledge and real-world experience, while presenting students with natural conversational language, idiomatic expressions, and communication skills.